Posted by ann :) on Thursday, September 13, 2012 at 7:25pm.
add the last two:
4x + 6y = -4
from the 1st: y = -2-2x
sub into above new equation:
4x + 6(-2-2x) = -4
4x - 12 - 12x = -4
-8x = 8
x = -1
then y = -2+2 = 0
in the 2nd:
solve the system
just need the steps how to do it
algebra - Solve the system of equations: what is the y-value in the solution? ...
College Algebra - Solve the system of equations using matrices. If system has no...
Algebra - Checking a few answers to some algebra problems: 1.Find the slope of ...
algebra - solve each system by substitution 1. 6x-3y=-33 2xty=-1 2. 2x-y=7 3x-2y...
algebra 2 - solve each system by substitution 1. 6x-3y=-33 2xty=-1 2. 2x-y=7 3x-...
Math - solve each system 1) 3x + y = 6 2x + 3y = 13 2) 2x + 5y - 6 = 0 -2x + y...
Algebra 2 - Solve the system using any algebraic method. 22.)2x-5y=4 23.)5x+7y=...
Algebra 2 Helpp :( - QUESTIONS (vvv) (1) Solve the system by subsitution 2x + y...
Intermediate Algebra - Solve using the substitution method. Show your work. If ...
algebra - addition method:3x-5y=-2 and 5y-2x=-2 how would I solve it since they ...
For Further Reading